Systematic review with meta‐analysis: comparative risk of lymphoma with anti‐tumour necrosis factor agents and/or thiopurines in patients with inflammatory bowel disease. Issue 8 (25th August 2020) - Chupin, Antoine; Perduca, Vittorio; Meyer, Antoine; Bellanger, Christophe; Carbonnel, Franck; Dong, Catherine
Summary: Background: The risk of lymphoma in patients with inflammatory bowel disease (IBD) treated with anti‐TNF agents remains unclear. Aim: To assess the comparative risk of lymphoma with anti‐TNF agents and/or thiopurines in IBD Methods: We searched PubMed, EMBASE and Cochrane Library to identify studies that evaluated lymphoproliferative disorders associated with anti‐TNF agents with or without thiopurines. The risk of lymphoma was assessed through four comparator groups: combination therapy (anti‐TNF plus thiopurine), anti‐TNF monotherapy, thiopurine monotherapy and control group. Pooled incidence rate ratios (IRR) were estimated through Poisson‐normal models. Results: Four observational studies comprising 261 689 patients were included. As compared with patients unexposed to anti‐TNF and thiopurines, those exposed to anti‐TNF monotherapy, thiopurine monotherapy or combination therapy had pooled IRR (per 1000 patient‐years) of lymphoma of 1.52 (95% CI: 1.06‐2.19; P = 0.023), 2.23 (95% CI: 1.79‐2.79; P < 0.001) and 3.71 (95% CI: 2.30‐6.00; P ≤ 0.01), respectively. The risk of lymphoma associated with combination therapy was higher than with thiopurines or anti‐TNF alone with pooled IRR of 1.70 (95% CI: 1.03‐2.81; P = 0.039) and 2.49 (95% CI: 1.39‐4.47; P = 0.002), respectively. The risk did not differ between anti‐TNF monotherapy and thiopurine monotherapy with pooled IRR of 0.72 (95% CI: 0.48‐1.07; P = 0.107). All observational studies were of high quality according to the Newcastle‐Ottawa scale. Conclusions: There is an increased risk of lymphoma in IBD patients treated with anti‐TNF agents, either alone or when combined with thiopurines.